1954
DOI: 10.1039/jr9540003922
|View full text |Cite
|
Sign up to set email alerts
|

The hydrated tetrafluorides of uranium and plutonium

Abstract: The tetrafluorides of uranium and plutonium form two hydrates, the higher one having 2-5 molecules of water per metal atom and the lower one 2.0 molecules of water or less. Methods for their formation have been investigated.The lower hydrate is pseudo-cubic, a = 5.69 kX for the uranium and 5.63 kX for the plutonium compound, and the proposed structure is similar to that of uranium dioxide, the water molecules occupying vacant uranium sites and being hydrogen-bonded to the fluorine. Very little change of cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Water can also occupy vacancy sites of the U 4+ ion to form two hydrate phases: the pseudo-cubic UF4(H2O)n where 0.5 ≤ n ≤ 2 and UF4(H2O)2.5. 13,14 The 2.5 hydrate, which has been minimally characterized to-date, has been shown to form when anhydrous UF4 is placed in dilute aqueous HF solutions. 15,16 The pseudo-cubic phase, which is a derivative of the CaF2-type phase, can form from a number of reactions, including electrolytic reduction of uranyl fluoride (UO2F2) in aqueous hydrofluoric acid, 17,18 addition of aqueous hydrofluoric acid to aqueous uranium tetrachloride (UCl4), 19 and hydration of UF4 formed from various dehydration reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water can also occupy vacancy sites of the U 4+ ion to form two hydrate phases: the pseudo-cubic UF4(H2O)n where 0.5 ≤ n ≤ 2 and UF4(H2O)2.5. 13,14 The 2.5 hydrate, which has been minimally characterized to-date, has been shown to form when anhydrous UF4 is placed in dilute aqueous HF solutions. 15,16 The pseudo-cubic phase, which is a derivative of the CaF2-type phase, can form from a number of reactions, including electrolytic reduction of uranyl fluoride (UO2F2) in aqueous hydrofluoric acid, 17,18 addition of aqueous hydrofluoric acid to aqueous uranium tetrachloride (UCl4), 19 and hydration of UF4 formed from various dehydration reactions.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The pseudo-cubic phase, which is a derivative of the CaF2-type phase, can form from a number of reactions, including electrolytic reduction of uranyl fluoride (UO2F2) in aqueous hydrofluoric acid, 17,18 addition of aqueous hydrofluoric acid to aqueous uranium tetrachloride (UCl4), 19 and hydration of UF4 formed from various dehydration reactions. 13,14 One report has even shown that UF4(H2O)n might hydrate as low as n = 0.4. 20 Elevated-temperature interactions of UF4 and water produce a variety of compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Less successful attempts to apply alternative methods for producing metallic plutonium did prove successful in preparing new plutonium phases in some cases; for example, the sodium vapor reduction of PuF 4 resulted in the novel phase (NaPuF 4 ) 1.5 . As part of an effort in the 1940s and 1950s to expand on and characterize the plutonium fluoride family, Zachariasen and Dawson et al . reported on the first crystal structures of several binary and ternary plutonium fluorides and oxyfluorides.…”
Section: Figurementioning
confidence: 99%
“…However characterization of actinide fluorides has typically favored the fully oxidized +6 complex (UF 6 ) due to the relevance as the uranium enrichment feedstock within various nuclear enterprises. [3][4][5] As such UF 6 has been extensively studied both within the context of chemistry and LDRD-2016-00031 LDRD Report chemical engineering; with recent focus on the hydrolysis product, uranyl fluoride, and the synthesis and characterization of various forms of uranyl fluoride hydrates. [6][7][8][9][10][11][12] The hydrolysis of the UF 6 is challenging physical chemistry problem and prior research has typically focused on the reaction products (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…3 Many of the UF 4 hydrates were synthesized via the reduction of U +6 , or suspensions of UF 4 with aqueous hydrofluoric acid. 5,16 Other methods to produce UF 4 hydrates have involved application of thermal energy to liberate structurally bound water from the 2.5 hydrate; however these methods can be complicated by the unintended production of uranyl fluorides (UO 2 F 2 •xH 2 O) and/or uranium oxides (UO 2 ; U 3 O 8) . 5,17 The primary characterization method of prior work has been single crystal and powder X-ray diffraction, although other characterization methods have been utilized, including Infrared (IR) spectroscopy and NMR, those efforts had not unambiguously identified the material crystal structure.…”
Section: Introductionmentioning
confidence: 99%